Renewable energy power for a sustainable future - Boyle, Godfrey (Oxford University Press, 2012)
The underlying physical and technological principles behind deriving power from direct solar (solar thermal and photovoltaics), indirect solar (biomass, hydro, wind and wave) and non-solar (tidal and geothermal) energy sources are explained, within the context of their environmental impacts, their economics and their future prospects.